Faktor yang Berhubungan Pelaksanaan Pendokumentasian Asuhan Keperawatan Di Ruang Rawat Inap Rumah Sakit Ernaldi Bahar Provinsi Sumatera Selatan - raden surahmat; Meilisa Dwiyanti; Mareta Akhriansyah; Amalia Amalia (Riset Informasi Kesehatan, 2021)
Background: Not maximally documenting nursing care will have an impact on the quality of nursing services. Methods: This study aims to determine what factors are associated with the implementation of nursing care documentation using quantitative methods, using a cross sectional approach, with a sample of 71 respondents. Results: From the results of this study obtained from 71 respondents whose early adulthood were 38 people (53.5%), female gender were 41 people (57.7%), professional education 36 people (50.7%), work period â‰¥2 years totaling 51 people (71.8%), good knowledge 50 people (70.4%), light workload 43 people (60.6%), implementation of good nursing documentation 46 people (64.8%), the results of bivariate analysis obtained age p value 0.003, gender Ï value = 0.041, education Ï value = 0.057, tenure Ï value = 0.012, knowledge Ï value = 0.001, workload Ï value = 0.018. Conclusion: Based on the results of the study it can be concluded that the age with early and late adulthood has a different mindset in work, while the implementation of documenting nursing care between men and women has its own way of differences in roles and responsibilities, with a high level of education with experience. good knowledge is obtained